Nonlinear Perron-Frobenius theory - Lemmens, Bas (Cambridge tracts in mathematics, 2012)
"Sometimes in mathematics an innocent-looking observation opens up a new road to a fertile field. A nice example of such an observation is due to Garrett Birkhoff [23] and Hans Samelson [187], who remarked that one can use Hilbert's (projective) metric and the contraction mapping principle to prove some of the theorems of Perron and Frobenius concerning eigenvectors and eigenvalues of nonnegative matrices. This idea has been pivotal for the development of nonlinear Perron-Frobenius theory"--